2009
DOI: 10.1262/jrd.20227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Semen Extenders and Storage Temperatures on Characteristics of Frozen-Thawed Bryde's (Balaenoptera edeni) Whale Spermatozoa

Abstract: Abstract. The present study investigated effects of three semen extenders and storage temperatures on post-thaw characteristics of Bryde's whale spermatozoa. Spermatozoa were collected from the vasa deferens of three mature Bryde's whales captured during the Japanese whale research in the north-west Pacific (May to August 2007) after death. The three semen extenders used for freezing were 1) a commercialized synthetic extender (AndroMed: AM), 2) Trisbased + 10% bovine serum albumin (BSA) and 3) Tris-based + eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Furthermore, the percentages of intact plasma membrane and motility were better than controls at 72 h in the presence of BSA and FCS in this study. These results are in agreement with the previous results in ram [31], whale [23], turkey [8], and buffalo [18] semen. These studies showed that BSA significantly improved semen characteristics.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the percentages of intact plasma membrane and motility were better than controls at 72 h in the presence of BSA and FCS in this study. These results are in agreement with the previous results in ram [31], whale [23], turkey [8], and buffalo [18] semen. These studies showed that BSA significantly improved semen characteristics.…”
Section: Discussionsupporting
confidence: 94%
“…The results also demonstrated that the effective conservation time was more than 6.5 days, and sperm motility achieved 75% after 3 days conservation. These results were in agreement with previous studies about ram (Matsuoka et al 2006), whale (Hiwasa et al 2009), buffalo (El-Kon 2011) and rabbit (Sarıozkan et al 2013). These studies suggested that BSA could improve sperm motility significantly after preservation.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies found that serum albumin could largely prevent these effects (Suter et al 1979). Bovine serum albumin (BSA) is a kind of serum albumin which could protect sperm efficiently (Matsuoka et al 2006;Hiwasa et al 2009;El-Kon 2011;Osman et al 2012;Sarıozkan et al 2013).…”
Section: Introductionmentioning
confidence: 99%